An Analysis of the Stigma of Children Born Out of Wedlock and the Formation of Trauma in the Character Hanun in Isrina Sumia’s Novel Dia yang Haram Based on Freudian Psychoanalysis: Stigma Anak di Luar Nikah dan Pembentukan Trauma Tokoh Hanun dalam Novel Dia yang Haram Karya Isrina Sumia: Kajian Psikoanalisis Freud - Bidadari Sakti; Irianto Ibrahim; La Ode Akhiri Zulzaman; Saidiman (CASA CENDEKIA MEDIA, 2026)
The study of literary psychology often uses Freud’s psychoanalysis merely to classify the id, ego, and superego, while the social dimensions that shape characters’ psychological wounds are less critically explored. This study aims to explain how the stigma of being born outside marriage shapes Hanun’s trauma in Isrina Sumia’s novel Dia yang Haram and how Freud’s personality structure operates in the processes of injury, self-defense, and resilience. This research used a descriptive qualitative design with a literary psychology approach. The primary data source was the novel Dia yang Haram, while secondary data included books and journal articles on psychoanalysis, social stigma, trauma, and resilience. Data were collected through reading, note-taking, thematic coding, and quotation documentation, then analyzed through data reduction, categorization, psychoanalytic interpretation, and conclusion drawing. The findings show that Hanun’s trauma emerges through verbal and social stigma, family rejection, emotional neglect, and internalized shame. These findings imply that Hanun’s inner conflict reflects the intersection of social stigma, unequal family relations, and the struggle to rebuild self-worth.